The Influence of Financial Literacy and Fintech Usage on Investment Interest Among Generation Z in Jakarta: The Mediating Role of Financial Self-Efficacy - Frimayasa, Agtovia; Pandin, Maria Yovia R; Kusmaningtyas, Amiartuti (Sean Institute, 2025)
This study aims to analyze the influence of financial literacy and fintech usage on investment interest among Generation Z in Jakarta, with financial self-efficacy as a mediating variable. Using a quantitative explanatory research design, data were collected from 100 respondents aged 18–27 through purposive sampling. Structural Equation Modeling using SmartPLS was employed to test direct and indirect relationships among variables. The results reveal that both financial literacy and fintech usage significantly influence investment interest, with fintech usage showing the strongest effect. Financial self-efficacy also plays a significant mediating role, bridging the gap between knowledge, technology access, and investment behavior. These findings highlight the importance of combining financial education, digital access, and psychological empowerment to enhance investment participation among youth. The study contributes to behavioral finance literature and provides insights for policymakers and fintech developers in designing inclusive and confidence-building financial programs for young investors.